Penentuan Konsentrasi Tanah Dalam Air Sungai Berdasarkan Perbedaan Warna - Imam Sofi'i (Jurnal Keteknikan Pertanian, 2008)
Information of soil erosion is very useful related with prevention action and planning in the future. The objective of this research is to determine soil concentration in water river based on colour differences using image processing and artificial neural network (ANN). Soil and water mixture image was taken using a digital camera then was processed by an image processing program. Two ANN Models were developed. The first model had 3 input parameters while the second model had 6 input parameters. Both models had altogether one output parameters of the soil concentration. The accuracy of the first model was 38% while the second one was 36%. Keywords: Soil and Water mixture, image processing, ANNDiterima: 12 Maret 2008; Disetujui: 20 Juni 2008